Oxygen Saturation Profiles in Healthy Term Infants in Early Postnatal Life - Goetz, Elizabeth M.; Tomlin, Brandon D.; Rinaldo, Kathryn E.; Baumann-Blackmore, Nicole L.; Petro, Rachel L.; Smith, Beth B.; Zapata, Jasmine Y.; Lasarev, Michael R.; McBride, Elizabeth B.; Kaluarachchi, Dinushan C. (American Journal of Perinatology, 2022)
Objective Oxygen saturation profiles generated by pulse oximetry are used as a clinical tool in the neonatal intensive care unit (NICU). There is limited evidence on normal oxygen saturation profile values in term infants. This study aimed to determine oxygen saturation profiles over an 8-hour monitoring period among healthy term neonates between 24 and 48 hours after birth.Study Design A prospective cohort study of healthy term neonates born at 37 to 41 weeks of gestation. Preductal oxygen saturations were continuously monitored for an 8-hour period between 24 and 48 hours of life using pulse oximetry. Oxygen profile histograms were recorded for analysis. The average percent oxygen saturation (SpO2) was measured over the entire study duration for each neonate and was characterized as the fraction of time of their SpO2 reading was in each of five intervals: ≤80, 81 to 84, 85 to 89, 90 to 94, and 95 to 100%.Results Seventy-five neonates were included in the study. Median SpO2 was 95.4%. Percentage time spent in each of the five SpO2 intervals was as follows: 0.07 (≤80), 0.15 (81–84), 0.88 (85–89), 26.9 (90–94), and 67.3% (95–100%). Eighteen infants (24%) spent the highest percentage of time in SpO2 of 90 to 94%.Conclusion This study provides reference ranges for oxygen profiles in healthy term neonates during 24 to 48 hours of life. Nearly one-quarter of newborns spent the highest percentage of time in SpO2 of 90 to 94%. This data is important when interpreting oxygen saturation profiles of term neonates admitted to the NICU.Key Points
Keywords: oxygen saturation; histogram; term newborns; saturation profiles